Diseño y construcción de un banco para pruebas de caracterización de los principales parámetros de generadores eléctricos para el AEIRNNR de la UNL. - Calle Chamba, Fabián Geovanny (2010)
The present project describes the design and construction of a bank of generators synchronous of rotor of salient poles, as a support to the academic pensum of the career of Engineering in Electromechanical, especially to the unit of Electric machines II. Most of central of electric generation uses this type of generators it is for that reason that the project was focused in this type of generators. Our project approaches the electric power generation, using as primotor to a motor of induction trifásico controlled by a variador of frequency. You gathers detailed information for the realization of the investigation, next the appropriate design settled down based on mathematical calculations basing us of the suggestions of professionals of this field. Designed the system, was carried out the construction of the bank, assembly and operation of the same one, as well as outlines, drawings and programming of the practices finally shows up the technician-economic and environmental valuation, also operation manual and maintenance of the automated prototype.